UNHAS-UiTM : renal pharmacy research collaboration meeting / Andi Anggriani and Nana Juniarti Natsir Djide - Anggriani, Andi; Natsir Djide, Nana Juniarti (Faculty of Pharmacy, 2024)
From October 14 to October 26, two lecturers from the Faculty of Pharmacy, Hasanuddin University (UNHAS) participated in a strategic joint research program with the faculty, aimed at bolstering research capabilities, enhancing manuscript writing skills, and expanding global collaborations. Both Ms. Andi Anggriani and Ms. Nana Juniarti Natsir Djide were selected for this prestigious program, supported by the Joint Research Program funding scheme from UNHAS. Ms. Anggriani, an expert in clinical pharmacy, has a history of successful collaborations with UiTM’s Dr. Norkasihan Ibrahim, particularly in renal pharmacy research. Ms. Nana, specialising in pharmaceutical microbiology, is at the forefront of establishing a new research partnership with Dr. Norkasihan. The program commenced with a focused discussion on the work schedule and the next steps for ongoing manuscript publications. Ms. Andi Anggriani and Ms. Nana Juniarti Natsir Djide write about their experience during their visit here.